(untitled) - Ľubica Bánovčinová; Zuzana Škodová (University of Ostrava, 2022)
Aim: The aim of our study was to examine the impact of partner support and perceived stress on the level of depressive symptoms in the postpartum period. Design: Cross-sectional observational study. Methods: A total of 206 women were included in the study. The mean age of respondents was 30.9 years (SD = 4.8; range: 20-44 years.). The Edinburgh Postnatal Depression Scale, Postpartum Partner Support Scale, and Perceived Stress Scale were used to measure the main observed variables. The questionnaire was supplemented with socio-demographic, health-related, and obstetric data. Results: The linear regression model showed that significant predictors of postpartum depression were: lack of support person during labor [β = -0.105; 95% CI = (-0.754; -0.030)]; lower education [β = -0.139; 95% CI = (-2.256; -0.407)]; lower partner support [β = -0.154; 95% CI = (-0.115; -0.025)]; and higher perceived stress [β = 0.755; 95% CI = (0.470; 0.615)]. Perceived stress was deemed to be the most significant predictor of increased depressive symptoms. Conclusion: Identifying mothers who perceive low support from their partner, or who experience high levels of stress and depression, and, subsequently, offering effective psychological support is important in helping to maintain the psychological and mental wellbeing of mothers.